Probiotics : how does it affect our health? - Abrahamsson, Julia (SLU/Department of Molecular Sciences, 2018)
The human body consists of about 10 times as many bacteria as our own body cells. Only the gastrointestinal tract can hold up to 400 different bacterial species, where the majority of the bacteria are concentrated to the large intestines. We are born sterile without any microbiota, but thereafter colonizing and development of the microbiota occur over time. Probiotics are good bacteria that are supplied via food or as dietary supplements. The most common of probiotic bacteria belongs to the genera Lactoba-cillus or Bifidobacterium. They are classified as safe bacteria which makes them very popular to use in probiotic products. Both genera are Gram positive, rod-shaped and can ferment carbohydrates to short-chain fatty acids that lower the pH and make it unfavorable for other bacteria. Some guidelines for probiotics are that it must contain live bacteria and be resistant to gastric acid and bile salts.